Hesperidin Methyl Chalcone Reduces the Arthritis Caused by TiO2 in Mice: Targeting Inflammation, Oxidative Stress, Cytokine Production, and Nociceptor Sensory Neuron Activation - Nayara A. Artero; Marília F. Manchope; Thacyana T. Carvalho; Telma Saraiva-Santos; Mariana M. Bertozzi; Jessica A. Carneiro; Anelise Franciosi; Amanda M. Dionisio; Tiago H. Zaninelli; Victor Fattori; Camila R. Ferraz; Maiara Piva; et al. (Molecules, 2023)
Arthroplasty is an orthopedic surgical procedure that replaces a dysfunctional joint by an orthopedic prosthesis, thereby restoring joint function. Upon the use of the joint prosthesis, a wearing process begins, which releases components such as titanium dioxide (TiO2) that trigger an immune response in the periprosthetic tissue, leading to arthritis, arthroplasty failure, and the need for revision. Flavonoids belong to a class of natural polyphenolic compounds that possess antioxidant and anti-inflammatory activities. Hesperidin methyl chalcone’s (HMC) analgesic, anti-inflammatory, and antioxidant effects have been investigated in some models, but its activity against the arthritis caused by prosthesis-wearing molecules, such as TiO2, has not been investigated. Mice were treated with HMC (100 mg/kg, intraperitoneally (i.p.)) 24 h after intra-articular injection of 3 mg/joint of TiO2, which was used to induce chronic arthritis. HMC inhibited mechanical hyperalgesia, thermal hyperalgesia, joint edema, leukocyte recruitment, and oxidative stress in the knee joint (alterations in gp91phox, GSH, superoxide anion, and lipid peroxidation) and in recruited leukocytes (total reactive oxygen species and GSH); reduced patellar proteoglycan degradation; and decreased pro-inflammatory cytokine production. HMC also reduced the activation of nociceptor-sensory TRPV1+ and TRPA1+ neurons. These effects occurred without renal, hepatic, or gastric damage. Thus, HMC reduces arthritis triggered by TiO2, a component released upon wearing of prosthesis.